Building the Chivalric Canon: Teofilo Folengo, Lodovico Domenichi, and Aretino's Silence. (3rd April 2019) - Faini, Marco
ABSTRACT: This article explores the 1552 posthumous edition of Teofilo Folengo's Macaronee, which included his masterpiece Baldus, and the preface to the work penned in late 1544/early 1545 by one Vigaso Cocaio. Following a suggestion by Luca Curti, who identified Vigaso with Lodovico Domenichi, I suggest including the Baldus in Domenichi's publication programme of chivalric novels. This included Pulci's Morgante and Boiardo's Inamoramento de Orlando, both published in 1545. I argue that Folengo was originally part of Domenichi's attempt at building a chivalric canon and I make some hypotheses as to why this programme was never fully accomplished. In doing so, I pay special attention to the relations between Domenichi, Folengo, and Pietro Aretino, suggesting that this latter may have played a role in the editorial history of Folengo's macaronic works.